Perbedaan Daya Hambat Ekstrak Etanol Daun Miana Merah Konsentrasi 10%, 20% Dan 30% Terhadap Pertumbuhan Bakteri Shigella dysentriae - Muhammad Yumni; Suwandi Edy (Indonesian Journal of Herbal and Biomedical Research, 2026)
The Miana plant is an easily cultivated ornamental species. In West Kalimantan, Miana grows abundantly in the wild and grows rapidly. Miana leaves contain bioactive compounds, including flavonoids, tannins, triterpenoids, and steroids, which serve as antibacterial agents. These phytochemicals can inhibit bacterial growth, particularly that of Shigella species. This study aimed to elucidate the differences in the inhibitory efficacy of various concentrations of Miana leaf ethanol extract on the growth of Shigella dysenteriae. A quasi-experimental research design was employed. The study used Miana leaf ethanol extract samples at three treatment concentrations (10%, 20%, and 30%), with 10 replications per concentration. The inhibitory activity against S. dysenteriae was evaluated using the Kirby-Bauer disk diffusion method. Laboratory results revealed that the mean zones of inhibition formed at concentrations of 10%, 20%, and 30% were 7.90 mm, 9.10 mm, and 11.10 mm, respectively. Statistical analysis using the Friedman test yielded a p-value of 0.000 (p < 0.05). Consequently, there is a significant difference in the antibacterial inhibitory activity of red Miana leaf ethanol extracts at 10%, 20%, and 30% concentrations against the growth of Shigella dysenteriae.